Cultural Origins of Japan’s Premodern Night Soil Collection System - Marta E. Szczygiel (Worldwide Waste, 2020)
Night soil collecting was practiced to different extents wherever urbanization developed. For example, Japan relied on human waste as fertilizer to the point it became a profitable business, while in most Western countries it was considered a necessary evil. What is the reason behind such different attitudes? In this paper, I apply David Inglis’ theory of a mode of excretion to premodern Japanese context in order to shed light on this phenomenon. First, informed by Mary Douglas, I propose slight alternations to the original theoretical framework of a mode of excretion so it emphasizes considerations of excreta in a culture’s cosmology. Next, I examine scatological content in the oldest chronicle of Japan: 'Kojiki'. Based on the analysis, I conclude the Japanese traditional notion of defecation is non-binary—it includes both positive and negative understandings of excrement. Most importantly, the notion lacks moral stigmatization; excrement is not kegare. Then, I characterize how defecation was practiced. Contrary to present norms, it was conducted relatively out in the open, without strict regularization. I argue it was because the notion was not stigmatized, thus there was no need to be particularly embarrassed about the body’s excretory capacities. Finally, I conclude the holistic approach to the notion and practice of defecation in Japan’s traditional fecal habitus is the reason why human waste could be viewed as productive and not merely an object of disgust. Thus, because of this cultural encoding, traditional means of excretory disposal in Japan relied on night soil collection.